Bending contact response of composite sandwich beam - Lim, Chong Heng. (2012)
The aim of this project is to investigate structural response of honeycomb sandwich beam subjected to bending loads. Face-core delamination is a common un-conventional failure mode of sandwich composites in aerospace structures. Sandwich beam specimens made of unidirectional carbon fibre face (16 ply each) and Nomex honeycomb core of 20mm height and 13mm cell size with different percentage of face-core delamination were fabricated, and three-point bending tests were performed on them. The effect of face-core delamination on the stiffness of a honeycomb sandwich beam was analysed. Results showed that increase in face-core delamination results in a reduction in the elastic stiffness of the beam. Each delaminated beam also exhibits multiple stiffness characteristics throughout the loading process. The relationship between the percentage of delamination and the change in stiffness of the beam throughout the course of bending test was established. The change in stiffness of the beam was quantified in two ways – the ratio of second stiffness to the first stiffness (K2/K1) and the ratio of the first stiffness of a delaminated beam to the first stiffness of a perfectly bonded beam (K1delaminated/K10% delamination).